Factors Influencing Temperature Fields during Combustion Reactions. Issue 3 (20th May 2014) - Kappagantula, Keerti; Crane, Charles; Pantoya, Michelle
Abstract A unique, non‐invasive diagnostic technique for characterizing two‐dimensional thermal fields generated during the combustion of nanothermites was developed. Temperature resolved thermal images of the reactions were obtained using infrared imaging coupled with multiwavelength pyrometry. Thermal images of fuel rich aluminum/copper oxide (Al/CuO) and aluminum/polytetrafluoroethylene (Al/PTFE) mixtures embedded with different additives were analyzed and the principal factors affecting the spatial distribution of temperature during their combustion were identified. Results showed two distinct temperature zones during combustion: a hot zone surrounding the point of ignition, where the highest temperatures were recorded followed by a lower temperature region called the intermediate zone. Temperatures are plotted as a function of distance from the point of ignition such that inflection points distinguishing temperature gradients provide an indication of the range of the thermal influence. Gas generation and heat of combustion are principal factors affecting temperature fields: greater gas generation in addition to condensed phase products promotes higher temperatures in the far field. Results also indicate that faster reactions attain higher temperatures and more extensive temperature fields. This observation is attributed to greater momentum of the gas and condensed phase products projected from the hot zone that shift the inflection point farther. These results show that multiphase convection is a governing mechanism promoting thermal energy distributions.